Acute Suppurative Otitis Media in Children with Risk Factors of Recurrent Upper Respiratory Tract Infection, Non-Exclusive Breastfeeding, and Working Mother - Rizky Amaliyah Putri; Nurul Hidayati (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2022)
Background: Many factors influence Children's health, including the mother's employment status and exclusive breastfeeding. Purpose: To present the case of children with OMSA (Acute Suppurative Otitis Media) and several risk factors for recurrent upper respiratory tract infection (URI), not getting exclusive breastfeeding, and working mothers. Case: A boy, one-year-old and four months, came to the family doctor's clinic with his mother. They were complaining of discharge from his right ear. The fluid has come out from the right ear since seven days ago and does not smell. He had a recurrent cold previously. He only gets exclusive breastfeeding for two months, and the mother was busy with work. On examination, there was a central perforation on the right ear tympanic membrane. He was treated with antibiotics and decongestants, then turned to an ENT specialist. After a home visit at two weeks of therapy, the tympanic membrane was closed. Conclusion: The importance of controlling risk factors to prevent recurring ASOM. ABSTRAK Latar Belakang: Kesehatan anak dipengaruhi oleh banyak faktor, salah satunya adalah status pekerjaan ibu dan pemberian ASI eksklusif. Tujuan: Untuk menyajikan kasus anak dengan OMSA (Otitis Media Supuratif Akut) dengan faktor resiko ISPA berulang, tidak mendapatkan ASI eksklusif, dan ibu yang bekerja. Kasus: Seorang anak laki-laki berusia 1 tahun 4 bulan datang dengan ibunya ke klinik dokter keluarga dengan keluhan keluar cairan dari telinga kanan. Keluar cairan dari telinga kanan ini sejak 7 hari yang lalu dan tidak berbau. Sebelumnya pasien mengalami pilek yang sering kekambuhan. Pasien hanya mendapatkan ASI eksklusif selama 2 bulan, dan Ibu sibuk bekerja. Pada pemeriksaan didapatkan perforasi sentral pada membrane timpani telinga kanan. Pasien diterapi dengan antibiotic dan decongestan, kemudian dirujuk ke dr Spesialis THT. Setelah dilakukan homevisit pada 2 minggu terapi, didapatkan membrane timpani sudah menutup. Kesimpulan: Pentingnya pengendalian faktor resiko untuk mencegah OMSA berulang. Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332710